Metasurface polarization splitter. (28th March 2017) - Slovick, Brian A.; Zhou, You; Yu, Zhi Gang; Kravchenko, Ivan I.; Briggs, Dayrl P.; Moitra, Parikshit; Krishnamurthy, Srini; Valentine, Jason
Abstract : Polarization beam splitters, devices that separate the two orthogonal polarizations of light into different propagation directions, are among the most ubiquitous optical elements. However, traditionally polarization splitters rely on bulky optical materials, while emerging optoelectronic and photonic circuits require compact, chip-scale polarization splitters. Here, we show that a rectangular lattice of cylindrical silicon Mie resonators functions as a polarization splitter, efficiently reflecting one polarization while transmitting the other. We show that the polarization splitting arises from the anisotropic permittivity and permeability of the metasurface due to the twofold rotational symmetry of the rectangular unit cell. The high polarization efficiency, low loss and low profile make these metasurface polarization splitters ideally suited for monolithic integration with optoelectronic and photonic circuits. This article is part of the themed issue 'New horizons for nanophotonics'.